The DNA replication initiation protein DnaD recognises a specific strand of the Bacillus subtilis chromosome origin - Winterhalter, Charles; Pelliciari, Simone; Stevens, Daniel; Fenyk, Stepan; Marchand, Elie; Cronin, Nora B; Soultanas, Panos; Costa, Tiago R D; Ilangovan, Aravindan; Murray, Heath (Nucleic acids research, 2023)
Abstract Genome replication is a fundamental biological activity shared by all organisms. Chromosomal replication proceeds bidirectionally from origins, requiring the loading of two helicases, one for each replisome. However, the molecular mechanisms underpinning helicase loading at bacterial chromosome origins (oriC) are unclear. Here we investigated the essential DNA replication initiation protein DnaD in the model organism Bacillus subtilis. A set of DnaD residues required for ssDNA binding was identified, and photo-crosslinking revealed that this ssDNA binding region interacts preferentially with one strand of oriC. Biochemical and genetic data support the model that DnaD recognizes a new single-stranded DNA (ssDNA) motif located in oriC, the DnaD Recognition Element (DRE). Considered with single particle cryo-electron microscopy (cryo-EM) imaging of DnaD, we propose that the location of the DRE within oriC orchestrates strand-specific recruitment of helicase during DNA replication initiation. These findings significantly advance our mechanistic understanding of bidirectional replication from a bacterial chromosome origin. Graphical Abstract Graphical Abstract In Bacillus subtilis, the basal unwinding sequence at the origin of replication oriC was known to comprise two DnaA boxes (DnaAboxes6/7, grey triangles) and a single-strand DNA binding region on the bottom strand (DnaA-trios, green triangles). The master initiator protein DnaA (green circles) binds both of these regions and can provide a scaffold to load a first helicase on bottom strand. Here we discovered a new element of the unwinding region located opposite the DnaA-trios and recognised by the replication protein DnaD, which we named the DnaD Recognition Element (DRE). We propose that binding of DnaD to the DRE promotes a second helicase loading event, providing a pathway to achieve bidirectional DNA replication initiation at a bacterial chromosome origin.